A Copper Iodide Cluster‐Based Metal–Organic Polyhedra for Photocatalytic Click Chemistry. Issue 5 (12th May 2022) - Wu, Yao; Xie, Mo; Jin, Ji-Kang; Zhang, Zhi-Yin; Hu, Han; Tian, You-Ping; Xiao, Yu-Qing; Ning, Guo-Hong; Li, Dan; Jiang, Xuanfeng
Abstract : Light‐Induced CuAAC Reaction In article number 2100155 by Guo‐Hong Ning, Dan Li, Xuanfeng Jiang, and co‐workers, a novel copper‐iodide cluster‐based metal–organic polyhedra (MOP) with half‐truncated cube topology is prepared through conformation‐adaptive self‐assembly strategy. This MOP containing unprecedent Cu3I3 cluster node highly exhibits photo‐catalytic activity towards CuAAC reaction under the WLED irradiation in water.